Democracy through improvisation: A theatre education approach (Pedagogical Horizons, 2025)
This article examines how democracy education can be implemented in everyday school life through theatre education methods, especially improvisation. Building on the concept of ‘democracy as a way of life’ (Himmelmann, 2004) and the teaching principle of political education, approaches to democracy education and theatre education are brought together. A teaching example illustrates how improvisational methods can promote democratic learning processes; practical tips provide teachers with ideas for their own use.
Keywords: theatre education; political education; democracy education